30,000 years of art : the story of human creativity across time and space. (New York : Phaidon, 2007)
From ancient Germany's "Lion Man of Hohlenstein-Stadel" to James Turrell's 1995 photograph "Roden Crater," chronologically presents one thousand examples of art from different countries, cultures, and civilizations and discusses what makes each piece both unique and representative.
Contents -- 1000 works of art -- Timelines -- Glossary -- Index.
Includes index.
Adult
Keywords: Art -- History; Art -- History; Art -- History -- Chronology; Kunst; Beeldende kunsten; Bildband